The Exceptional Grandeur of Small Objects: Paul Scott’s Ceramics - Reynier, Christine (Polysèmes, 2020)
Little known in France, Paul Scott has begun to make a name for himself in Britain and other countries such as Canada, Denmark or Norway, where several exhibitions of his artworks have been organised since the early 1990s. His is a humble art or craft – ceramics. Paul Scott makes blue and white teacups, plates and dishes in glazed ceramic, drawing on traditional patterns and decorative techniques, recycling and updating them to comment on our contemporary society. This paper deals with the uniqueness and originality of Paul Scott’s art. It both means to investigate Paul Scott’s unique dialogue with artists and practices of the past and the present, and to show how the ceramist reveals the exceptional grandeur of small objects. I will argue that by choosing to design tableware – plates and dishes, initially meant for food – Paul Scott places his art at the centre of a network connecting human beings and other living beings, devising a way-of-being-with-the-world, a way of inhabiting it and an art of living where ethical, environmental, political and aesthetic concerns come together. Corinne Pelluchon’s phenomenology, as developed in Nourishments, which comes in the wake of Derrida’s work, helps to illuminate Paul Scott’s relational conception of the subject and his deeply committed art, firmly anchored in today’s world.